Increasing the Reading Interest of Elementary School Students - Septianingrum, Vindi; Pradana, Agrissto Bintang Aji; Vigitm, Anisa (Prosiding University Research Colloquium, 2021)
Reading has an important social role in human life. Reading is not only a necessity for students, but also the needs of everyone. Through reading, knowledge can be obtained. In essence, reading is a bridge to understanding how big the world is. However, in the 21st century, it is not the ability to read students, but the lack of interest in reading, be it textbooks or other books. This is due to the students’ lack of understanding of the texts they read, lack of vocabulary mastery including not understanding how to read well in accordance with the objectives to be achieved. This article aims to identify ways to increase elementary students’ reading interest. The benefits of this article are knowing the importance of increasing reading interest, understanding the functions and benefits of reading, as well as the factors that hinder students’ reading interest, along with the role of parents, teachers, librarians, and the government.